2013
DOI: 10.1007/s11845-013-1025-8
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of care and prognosis in patients with lung cancer

Abstract: The delay in the diagnosis in our population seems to be excessively long. The greater the age, a more advanced tumour stage, male sex, and poor general health status are associated with shorter delays. A longer treatment delay is associated with a longer survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…We know that disease severity of disease at the time of diagnosis affects the speed of medical decision making, with more advanced cancers having shorter delays to treatment, and smaller, early stage lung cancer associated with greater delays [12]. Our finding that larger tumors had shorter delays in care echoes multiple prior papers that have shown that larger tumors or more advanced cancers receive more timely care [11, 12, 18, 20, 22, 32]. …”
Section: Commentsupporting
confidence: 64%
See 1 more Smart Citation
“…We know that disease severity of disease at the time of diagnosis affects the speed of medical decision making, with more advanced cancers having shorter delays to treatment, and smaller, early stage lung cancer associated with greater delays [12]. Our finding that larger tumors had shorter delays in care echoes multiple prior papers that have shown that larger tumors or more advanced cancers receive more timely care [11, 12, 18, 20, 22, 32]. …”
Section: Commentsupporting
confidence: 64%
“…Our diagnosis and treatment delays are longer than others reported in the literature, particularly from those in populations outside the United States [10, 1820]. Another single VA facility reported a median of 48 days from presentation to diagnosis and 22 days from diagnosis to treatment [21].…”
Section: Commentmentioning
confidence: 75%
“…For that reason, it is not surprising that the association between survival and wait time in advanced-stage disease is reversed. Gonzalez-Barcala et al 38 reported that patients with advanced-stage disease have a shorter treatment delay and that a longer treatment delay was associated with longer survival. However, we cannot exclude the possibility that cancer biology might play a role in that association.…”
Section: Discussionmentioning
confidence: 99%
“…All remaining text was reviewed and direct and indirect evidence was selected and presented in evidence tables for final review and core panel discussion. With the exception of one single-center retrospective observational study related to PICO question 2, 5 and 13 studies related to PICO question 5, [6][7][8][9][10][11][12][13][14][15][16][17][18] no other direct evidence was identified. Evidence was graded by the methodology team using the standard GRADE quality assessment tool categorized as high, moderate, low, or very low.…”
Section: Study Selection and Evidence Assessmentmentioning
confidence: 99%
“…56 A supplemental literature review identified 13 additional references. [6][7][8][9][10][11][12][13][14][15][16][17][18] The methodology of the studies, the definitions used, and the evidence quality precluded arriving at a point estimate of the effect of time delay on outcomes. Issues included varying definitions of when cancer was first identified (eg, symptoms vs imaging vs tissue diagnosis), which interval was relevant (eg, symptoms to treatment vs diagnosis to treatment), heterogeneity in populations (eg, surgically treated vs all patients with lung cancer), differences in histology (eg, all types vs non-small cell lung cancer), intractable problems because of residual confounding within groups, confounding by indication (eg, sicker patients seen more rapidly), selection bias, and failure to adjust for lead time bias (eg, measuring survival from time of treatment rather than time of presentation).…”
Section: Remarksmentioning
confidence: 99%